2002
DOI: 10.1007/s10152-001-0100-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effects of current velocity on mussel feeding and mussel bed stability using an annular flume

Abstract: An annular flume was used to measure the effect of increasing current velocity on mussel (Mytilus edulis) feeding rate and the stability of mussel beds sampled from the mouth of the Exe estuary (SW England). It was found that, in contrast to earlier flume studies, the feeding rates of mussels from open coast sites were unaffected by current velocities up to 0.8 m s -1 . Algal cell depletion in the water column above mussels was a function of current velocity, increasing with declining currents below 0.05 m s -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 18 publications
4
68
1
Order By: Relevance
“…This hypothesis concurs with an extensive body of literature reporting that depletion of the algae in lower water layers limits the growth of mussels in real (Frechette and Bourget 1985;Newell 1990;Muschenheim and Newell 1992;Frechette and Despland 1999;Dolmer 2000) and artificial conditions (Wildish and Kristmanson 1984;Widdows et al 2002). Moreover, mussels were found to generate local heterogeneity in the concentration of algae in the lower water layers, even on spatial scales of !10 m (Asmus et al 1992;L.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This hypothesis concurs with an extensive body of literature reporting that depletion of the algae in lower water layers limits the growth of mussels in real (Frechette and Bourget 1985;Newell 1990;Muschenheim and Newell 1992;Frechette and Despland 1999;Dolmer 2000) and artificial conditions (Wildish and Kristmanson 1984;Widdows et al 2002). Moreover, mussels were found to generate local heterogeneity in the concentration of algae in the lower water layers, even on spatial scales of !10 m (Asmus et al 1992;L.…”
Section: Discussionsupporting
confidence: 89%
“…A significant body of literature exists that shows that, in soft-sediment or subtidal mussel beds, algal food availability limits intake by mussels (Wildish and Kristmanson 1984;Dolmer 2000;Widdows et al 2002) and mussel growth (Frechette and Bourget 1985;Page and Hubbard 1987;Newell 1990;Muschenheim and Newell 1992;Frechette and Despland 1999;Oie et al 2002). Dislodgment and predation depend strongly on local mussel density (Bertness and Grosholz 1985;Okamura 1986;Cote and Jelnikar 1999;Hunt andScheibling 2001, 2002) because nearby conspecifics are the main substrate for attachment on soft-bottom sediment.…”
Section: A Simple Spatial Modelmentioning
confidence: 99%
“…In particular subtle changes in speed and force of the tidal currents leave traces in the granulometry of associated sediments. In addition, biological factors like seagrass coverage (Ward et al 1984;Fonseca and Fisher 1986;Heiss et al 2000), mussel beds (Widdows et al 2002) or the presence of the lugworm Arenicola marina (Wohlenberg 1937;Volkenborn and Reise 2006) can have a signiWcant impact on the sediment composition. Changes in the grain size composition of Wadden Sea sediments can also be man-made.…”
Section: Introductionmentioning
confidence: 99%
“…Suitable substrates with high stability might consist of solid material such as rocks, or artificial structures (such as floating spat mussel collectors), but can also be sedimentary, such as macrophytes, shell material, or pebbles (Seed 1976, Witman & Suchanek 1984, Dankers & Zuidema 1995, Widdows et al 2002, Kangeri et al 2014. Several studies have suggested that beds with older mussels are a preferred settlement substrate, adding to the rejuvenation of existing mussel beds (Herlyn & Millat 2000, Dare et al 2004, Dolmer & Stenalt 2010, Commito et al 2014).…”
Section: Conceptual Model Of the Human-natural System Of Mussel Culturementioning
confidence: 99%
“…Mussels can thereby maintain filtration at current velocities up to 0.8 m s-1 (Widdows et al 2002). Furthermore, vertical mixing is enhanced by the roughness of the sea floor and thereby enhanced by the structural complexity of the mussel bed, thus exerting a positive feedback loop of mussels on their food transport (Fréchette et al 1989, Wiles et al 2006, Saurel et al 2013, Folmer et al 2014.…”
Section: Bottom-up: Food and Water Transport Growthmentioning
confidence: 99%